Budget Analysis As An Effort In Planning And Controlling Project Costs At PT. Kartika Jaya Prakasa - Hurriyaturrohman, Hurriyaturrohman; Fitri, Mia Auliatul; Nurhanifah, Risdiani; Bahri, Saepul; Noor Haffitri, Shinta Dewi (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2024)
This study aims to analyze the role of the budget as a tool for planning and controlling project costs at PT Kartika Jaya Prakasa. In the competitive world of construction business, effective budget management is essential to ensure project efficiency and success. This research uses a qualitative descriptive approach with a case study method, which includes interviews, direct observation, and documentation analysis. The results showed that the company had implemented various cost control techniques, such as a budget monitoring system and cost variance analysis, which helped keep expenditures within budget. However, the company faces challenges such as economic uncertainty, limited resources, and resistance to change. Recommendations include increased training, adoption of technology, and development of a supportive corporate culture. With these measures, PT Kartika Jaya Prakasa is expected to improve budget efficiency and achieve better project success in the futur.